Problematic Issues of Protecting Property Rights from Illegal Actions of Public Authorities - K. I. Varava (Bulletin of Kharkiv National University of Internal Affairs)
Property right is one of the key legal institutions of society, and the protection of property right plays an important role in guaranteeing this institution. The issue of protection of property right remains problematic, when there is a conflict of interest between bona fide purchasers and original owners, especially in cases where the original owner is the state or local community, which misused the property and therefore, initiated the process of illegal transfer of the property right. There are serious differences in law-enforcement practice regarding the views on resolving disputes over the recovery of state or municipal property from bona fide purchasers. The most problematic in these cases is the establishment whether the property was taken out of the possession of the owner or the person to whom he transferred the property into possession, not on their will (paragraph 3 of Part 1 of the Art. 388 of the Civil Code of Ukraine). They usually try to prove the illegality of the decision of public authorities or local self-government agency in these cases and that their actions were committed in excess of authority.